2017
DOI: 10.1155/2017/9207616
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Evaluation of Vimentin Expression in Correlation with Ki67 and CD44 in Surgically Resected Pancreatic Ductal Adenocarcinoma

Abstract: Purpose. Radical surgical resection with adjuvant chemotherapy or chemo-radiotherapy is the most effective treatment for pancreatic ductal adenocarcinoma (PDAC). However, relatively few studies investigate the prognostic significance of biological markers in PDAC. This study aims to look into the expressions of vimentin, Ki67, and CD44 in PDAC surgical specimens and their potential prognostic implications in survival. Method. The study was designed as retrospective, and vimentin, Ki67, and CD44 expressions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…However, the loss of Ecadherin is usually exclusively found in metastatic lesions and the vimentin is well known for non-specific, frequent coexpression in pancreatic cancers. Therefore, the feasibility as a prognostic marker seems to be limited although a few studies have suggested these as potential prognostic markers [22]. On the other hand, the EMT marker VEGF shares similar structural morphology with FGFRs, and both are very important for angiogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, the loss of Ecadherin is usually exclusively found in metastatic lesions and the vimentin is well known for non-specific, frequent coexpression in pancreatic cancers. Therefore, the feasibility as a prognostic marker seems to be limited although a few studies have suggested these as potential prognostic markers [22]. On the other hand, the EMT marker VEGF shares similar structural morphology with FGFRs, and both are very important for angiogenesis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely to E-cadherin, a positive correlation between UDC and vimentin and zinc finger E-box binding homeobox 1 (ZEB1) is observed by IHC [ 94 , 95 ]. Indeed, vimentin is a marker of mesenchymal features, while ZEB1 represents a transcriptional repressor of epithelial-to-mesenchymal transition (EMT) induction [ 96 , 97 ]. Since E-cadherin deficiency and vimentin/ZEB1 upregulation are associated with EMT mechanisms, it is not surprising that UDC is a particularly aggressive variant [ 98 ].…”
Section: Genetic and Molecular Features Of Pdac Variantsmentioning
confidence: 99%
“…Vimentin has been reported as the main intermediate lament protein of normal mesenchymal tissue [20], with a major role of sustaining cellular integrity [21]. Furthermore, vimentin expression was a potential independent adverse prognostic molecular marker in patients with pancreatic ductal adenocarcinoma [22]. Our nding of increased E-cadherin accompanied by decreased N-cadherin and vimentin in lncRNA AL161431.1 knockdown pancreatic cell lines clearly indicated that lncRNA AL161431.1 is critical in the EMT pathway.…”
Section: Discussionmentioning
confidence: 57%